Conceptualising the Learning of General Upper Secondary Students at Work - Krista Loogma; Birgit Peterson; Maret Aasa (Social Sciences, 2024)
The share of general upper secondary students working or having acquired work experience in an authentic work environment in parallel with learning in formal educational settings is expanding. It is therefore important to understand how learning in an authentic work environment and the interrelationships between work and school learning support the development of students. The main aim of this study is to understand and conceptualise the early work experience of students studying at general upper secondary schools. This study applies a phenomenological approach by conducting semi-structured interviews with students who have had work experience in authentic work environments. The main results of this study show that the variety of meaningful skills and competences developed in the work environment is rather great. Mostly, generic competences are learned at work. The incorporation of elements from one practice into the other (work to school or school to work) also occurs. Knowledge learned at school in traditional subjects and in elective courses is applied at work in a few cases. The positive impact of work experience on school studies, however, was reported—better time planning, increased motivation to learn, and increased career awareness.